PPAR gamma activation is neuroprotective in a Drosophila model of ALS based on TDP-43. - Joardar, A.; Menzl, J.; Podolsky, T.C.; Manzo, E.; Estes, P.S.; Ashford, S.; Zarnescu, D.C. (Human Molecular Genetics, 2015)
Amyotrophic Lateral Sclerosis (ALS) is a progressive neuromuscular disease for which there is no cure. We have previously developed a Drosophila model of ALS based on TDP-43 that recapitulates several aspects of disease pathophysiology. Using this model, we designed a drug screening strategy based on the pupal lethality phenotype induced by TDP-43 when expressed in motor neurons. In screening 1200 FDA-approved compounds, we identified the PPAR? agonist pioglitazone as neuroprotective in Drosophila. Here, we show that pioglitazone can rescue TDP-43-dependent locomotor dysfunction in motor neurons and glia but not in muscles. Testing additional models of ALS, we find that pioglitazone is also neuroprotective when FUS, but not SOD1, is expressed in motor neurons. Interestingly, survival analyses of TDP or FUS models show no increase in lifespan, which is consistent with recent clinical trials. Using a pharmacogenetic approach, we show that the predicted Drosophila PPAR? homologs, E75 and E78, are in vivo targets of pioglitazone. Finally, using a global metabolomic approach, we identify a set of metabolites that pioglitazone can restore in the context of TDP-43 expression in motor neurons. Taken together, our data provide evidence that modulating PPAR? activity, although not effective at improving lifespan, provides a molecular target for mitigating locomotor dysfunction in TDP-43 and FUS but not SOD1 models of ALS in Drosophila. Furthermore, our data also identify several 'biomarkers' of the disease that may be useful in developing therapeutics and in future clinical trials.